Profit Sharing Analysis on Mudharabah Savings to Increase Customer Interest in Microfinance - Haridah Haridah; M. Imam Muslim; Sulaiman Sulaiman (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2023)
Savings and Loans Cooperatives and Sharia Financing (KSPPS) NURI East Java Sokobanah 1 Sampang Branch has several products, both financing and savings. One of the KSPPS savings products is mudharabah savings. Members save their funds in microfinance and fully entrust the savings funds to be managed by microfinance in the hope of obtaining profit sharing. The income obtained by microfinance in throwing mudharabah savings funds will be divided according to the ratio agreement between the members and microfinance, 30% for customers and 70% for cooperatives. This study aims to determine the profit-sharing system in savings (mudharabah savings) carried out by the Microfinance East Java Sokobanah 1 Sampang. This research is qualitative research which is described by words or sentences that are separated according to categories to get a conclusion. Data collection used interviews with the manager of the Microfinance East Java Sokobanah 1 Sampang. The method of observation is to observe directly the financing activities in the field. The results of the study show that the increase in customer interest in mudharabah contract transactions does depend on the amount of profit sharing, namely on the highest ratio exceeding interest rates. The implication is that mudharabah contracts have the potential to be developed even though the risks are also great.